2007
DOI: 10.1123/ijsnem.17.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Eight Weeks of Aromatase Inhibition Using the Nutritional Supplement Novedex XT: Effects in Young, Eugonadal Men

Abstract: This study examined the effects of an aromatase-inhibiting nutritional supplement on serum steroid hormones, body composition, and clinical safety markers. Sixteen eugonadal young men ingested either Novedex XT or a placebo daily for 8 wk, followed by a 3-wk washout period. Body composition was assessed and blood and urine samples obtained at weeks 0, 4, 8, and 11. Data were analyzed by 2-way repeated-measures ANOVA. Novedex XT resulted in average increases of 283%, 625%, 566%, and 438% for total testosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Two studies have investigated the effects of aromatase inhibitors (androst-4-ene-3,6,17-trione) [240] and (hydroxyandrost-4-ene-6,17-dioxo-3-THP ether and 3,17-diketo-androst-1,4,6-triene) [241]. In both of these investigations, it was reported that free testosterone and dihydrotesterone levels were significantly increased.…”
Section: Dietary Supplements and Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have investigated the effects of aromatase inhibitors (androst-4-ene-3,6,17-trione) [240] and (hydroxyandrost-4-ene-6,17-dioxo-3-THP ether and 3,17-diketo-androst-1,4,6-triene) [241]. In both of these investigations, it was reported that free testosterone and dihydrotesterone levels were significantly increased.…”
Section: Dietary Supplements and Athletesmentioning
confidence: 99%
“…In both of these investigations, it was reported that free testosterone and dihydrotesterone levels were significantly increased. Muscle mass/fat free mass was not measured in one investigation [240] and no changes were observed in fat free mass in the other investigation [241]. …”
Section: Dietary Supplements and Athletesmentioning
confidence: 99%
“…Furthermore, aromatase inhibitors can minimise the side effects of anabolic steroids misuse [5]. Steroidal aromatase inhibitors, such as androst-4-ene-3,6,17-trione (6-OXO) [6], formestane [7] and androsta-1,4,6-triene-3,17-dione (ATD) [8], are marketed as nutritional supplements and are readily available via the internet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, steroidal aromatase inhibitors were also marketed as supplements 9–12. Products labeled as containing androsta‐1,4,6‐triene‐3,17‐dione have also been found on the market 13–15. Androsta‐1,4,6‐triene‐3,17‐dione has been reported to effectively reduce estrogen biosynthesis by irreversible aromatase inhibition 16, 17.…”
mentioning
confidence: 99%
“…Androsta‐1,4,6‐triene‐3,17‐dione has been reported to effectively reduce estrogen biosynthesis by irreversible aromatase inhibition 16, 17. Willoughby et al 13 investigated the effect of the supplement Novedex XT (labeled as containing 6,17‐keto‐etiocholeve‐3‐ol tetrahydropyranol, 3,17‐keto‐etiochol‐triene and Camellia sinensis ) on the serum concentrations of endogenous steroids in eugonadal men. Significant increases in dihydrotestosterone, free and total testosterone, and a decreased fat mass were reported during the 8‐week administration.…”
mentioning
confidence: 99%